2001
DOI: 10.1074/jbc.m007024200
|View full text |Cite
|
Sign up to set email alerts
|

Agrin-induced Activation of Acetylcholine Receptor-bound Src Family Kinases Requires Rapsyn and Correlates with Acetylcholine Receptor Clustering

Abstract: During neuromuscular synaptogenesis, neurally released agrin induces aggregation and tyrosine phosphorylation of acetylcholine receptors (AChRs) by acting through both the receptor tyrosine kinase MuSK (muscle-specific kinase) and the AChR-associated protein, rapsyn. To elucidate this signaling mechanism, we examined tyrosine phosphorylation of AChR-associated proteins, particularly addressing whether agrin activates Src family kinases bound to the AChR. In C2 myotubes, agrin induced tyrosine phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 56 publications
(100 reference statements)
2
75
0
Order By: Relevance
“…One candidate is the Src family of tyrosine kinases. Several studies have provided evidence that members of the Src family may be complexed with MuSK, rapsyn, and nAChRs in muscle, and that activation of the kinase produces receptor phosphorylation (Mohamed and Swope, 1999;Mittaud et al, 2001;Mohamed et al, 2001). The phosphorylation has been proposed as being important for receptor localization and stability, but this remains controversial (see article by S. Burden, this volume).…”
Section: Tethering Components To Neuronal Nicotinic Receptorsmentioning
confidence: 99%
“…One candidate is the Src family of tyrosine kinases. Several studies have provided evidence that members of the Src family may be complexed with MuSK, rapsyn, and nAChRs in muscle, and that activation of the kinase produces receptor phosphorylation (Mohamed and Swope, 1999;Mittaud et al, 2001;Mohamed et al, 2001). The phosphorylation has been proposed as being important for receptor localization and stability, but this remains controversial (see article by S. Burden, this volume).…”
Section: Tethering Components To Neuronal Nicotinic Receptorsmentioning
confidence: 99%
“…and Clustering-Agrin activation of MuSK leads to tyrosine phosphorylation of the AChR ␤-and ␦-subunits (13,26). The mechanisms that lead to tyrosine phosphorylation of the AChR are poorly understood and could, in principle, require glycosylation of MuSK.…”
Section: Fig 2 Mutation Of the Two Conserved N-linked Glycosylationmentioning
confidence: 99%
“…Although the signaling systems that induce AChR clustering in response to agrin and laminin have remained largely undefined, recent findings have suggested that formation of stable AChR clusters by both laminin and agrin require rapsyn, tyrosine phosphorylation of AChR ␤ and ␦ subunits and activation of Src-related kinases (Borges and Ferns, 2001;Ferns et al, 1996;Marangi et al, 2001;Marangi et al, 2002;Mittaud et al, 2001;Mohamed et al, 2001;Smith et al, 2001). A mechanism through which agrin and laminin couple these components to direct the lateral movement of AChR on the surface of postsynaptic muscle cells into nascent synapses, however, remains elusive.…”
Section: Introductionmentioning
confidence: 99%